Peranan Bahasa Dalam Berkesenian: Pemberdayaan Lirik Lagu sebagai Sarana Pembentukan Karakter Bangsa - Nurhaida Nuri (JURNAL ARBITRER, 2013)
Language has important role in supporting the activities of art of music.This support can be seen from the lyrics composing the song. Language is used as the media to express the artisticness of the music.The harmonious esthetical lyrics with the rhyme give certain meaning to the music lovers. Without proper lyrics, the music composed will lose their soul, except instrumentalities which have no lyrics. The language in this lyric  is categorized as literary words because it is ambiguous and full of expression. This kind of language may be used for several purposes, like persuading, to unite, to separate, and to provoke. Though the language is guaranteed by poetical license, as the literary work, such language is supposed to fulfill the esthetical aspects reflected in the intrinsic and extrinsic ones. As the lyric composer, a musician is bound the values and the social- ideology in society. No matter how, the lyric composer is part of the society. So, what happens in the society is part of his experience. The Indonesian proficiency as the media to express lyrics in Indonesian popular songs is undoubted. However, the quality is questioned. This worry comes up due to many lyrics-vulgarly expressed impacts negatively to the developing of national character. The success on building the character can be used through the role of Indonesian language, the model, especially the artists and musicians. They are forced to use the distinctive language bearing the character of honesty, politeness, and responsibility.